You are on page 1of 3

Series and Sequences –

Arithmetic and Geometric Progressions

Year 5 2009
Lecture Test 1 Total Marks: 25
__________________________________________________________________________________

2n
1 The sum of the first n terms of a series is given by 5 − .
5n−1
(i) Show that the series is a geometric series. [3]
(ii) Explain why this series converges and find its sum to infinity. [2]

 1   1   1   1 
2 Find  − + ( m − 1) d  +  − + md  +  − + ( m + 1 ) d  + K K +  − + (m + n )d  where m, n and d are
 2   2   2   2 
constants, leaving your answer in terms of m, n and d. [3]

3 The first term of an arithmetic series is 3 and the first term of a geometric series is 4. The arithmetic and
geometric series have both b as the common difference and common ratio respectively. The sixth term of
the arithmetic series is equal to the sum of the third and fourth terms of the geometric series. Find all the
possible values of b. For convergence in the geometric series, find its sum to infinity. [5]

4 Express 4 x − 3 − 4 x 2 in the form −( Ax + B ) 2 + C. [1]

Hence solve
( x 2 − 1)(4 x − 3 − 4 x 2 )
≥ 0,
( x 2 − 5)

5 A right circular cone with radius 3 cm and height 9 cm is initially full of water. Water is leaking from the

circular base of the cone at a rate of 2 cm3 s 1, find the exact rate of change of the depth of water when the
depth of water is 6 cm. [4]

END OF TEST
Solutions – Year 3 LT1 2009

2n
1(i) Sn = 5 −
5n −1
Tn = Sn − Sn −1
 2n   2n −1 
=  5 − n −1  −  5 − n−2 
 5   5 
n −1
2
= n −1 ( −2 + 5 )
5
n −1
 2
= 3  − − − − − (1)
5
n
2
3 
Tn +1 2
=  n −1 =
5
(constant)
Tn 2 5
3 
5
∴ series is a geometric series.

n −1
 2 n −1
Alt: Tn = 3   is in the form Tn = ar .
 5
∴ series is a geometric series.
Tn +1 2
1(ii) r= =
Tn 5
Since r < 1 , the series converges.

T1 3
S∞ = = =5
1− r 1− 2
5
2 no. of terms in the sum: n+2
n + 2  1   1 
sum =  − + ( m − 1) d  +  − + ( m + n) d  
2  2   2 
n+2
=  −1 + ( 2m + n − 1) d 
2 
3 3 + 5b = 4b 2 + 4b 3
4b + 4b 2 − 5b − 3 = 0
3

 3  1
 b +  ( b − 1)  b +  = 0
 2   2
3 1
b = − , b = 1, b = −
2 2
4 8
1 =
For b < 1 , b = − Sum to infinity = 1
2 1 − (− ) 3
2
4 x − 3 − 4 x 2 ≡ −(2 x − 1) − 2
2
4
( x 2 − 1)(4 x − 3 − 4 x 2 )
≥0
( x 2 − 5)
x2 −1
⇒ ≤ 0 Q (4 x − 3 − 4 x 2 ) < 0 for all x ∈ ¡ ⇒ − 5 < x ≤ −1 or 1 ≤ x < 5 .
x2 − 5
5 Volume of water V
1 1
= π ( 32 ) ( 9 ) − π r 2 ( 9 − h )
3 3
2
1 1 
= 27π − π  ( 9 − h )  ( 9 − h )
3 3 
π
( 9 − h)
3
= 27π −
27
dV π ( 9 − h )
2

=
dh 9
dh dh dV = 9 dV
= × .
( ) dt
2
dt dV dt π 9 − h
dV
Given = −2 cm3s −1 when h = 6 cm
dt
dh 9 2
∴ = ( −2 ) = − cm s−1
dt π ( 3) 2 π